2000
DOI: 10.1136/oem.57.2.116
|View full text |Cite
|
Sign up to set email alerts
|

The role of physical and psychological factors in occupational low back pain: a prospective cohort study

Abstract: Objective-To examine risk factors for onset of low back pain (LBP) in healthcare workers. Methods-Nursing students, during their 3 year training period, and 1 year after training were studied in a prospective cohort study, with repeated self reported measurements of determinants of LBP at 6 monthly intervals for 3 years during training, and after a 12 month interval there was an additional final follow up. Results-During training, increased risk of new episodes of LBP was associated with having had LBP at base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
127
3
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(142 citation statements)
references
References 23 publications
10
127
3
2
Order By: Relevance
“…A meta-analysis based on 229 studies on gender differences in caregiver psychological and physical health and caregiving stressors suggested that women had higher levels of burden and depression, and lower levels of subjective well-being and physical health [13]. An interesting prospective cohort study reported that the management of occupational low back pain might be improved by the management of psychological distress [33]. In the present study, the CES-D and the MHS used were based on SF-8 for the other outcome measurements; however, as with the results for low back pain, a meaningful effect was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis based on 229 studies on gender differences in caregiver psychological and physical health and caregiving stressors suggested that women had higher levels of burden and depression, and lower levels of subjective well-being and physical health [13]. An interesting prospective cohort study reported that the management of occupational low back pain might be improved by the management of psychological distress [33]. In the present study, the CES-D and the MHS used were based on SF-8 for the other outcome measurements; however, as with the results for low back pain, a meaningful effect was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…Interest has been increasing with respect to psychosocial factors relating to LBP during the past several years in occupational health research. Considerable evidence exists which indicates that social and psychosocial factors play a major role in the symptom complex of LBP 1,[3][4][5][6][7][8][9] . In Japan, although the incidence of illness from employment is declining, frequency of LBP maintains high rates 10) .…”
Section: Introductionmentioning
confidence: 99%
“…Feyer et al demonstrated that a high score for the general health questionnaire (GHQ) was related to low back pain (5). In this study the population had a good mental health status.…”
Section: Discussionmentioning
confidence: 66%
“…Feyer et al in Australia demonstrated that general health questionnaire (GHQ) with high score was a risk factor for low back pain (5). Roupa et al in Greece showed that 40% of nurses with some history of low back pain that had effects on their mood and sleep quality (6).…”
Section: Introductionmentioning
confidence: 99%